Calendrical variations in Second Temple Judaism : new perspectives on the "Date of the Last Supper" debate - Saulnier, Stéphane (Supplements to the Journal for the study of Judaism., 2012)
From a consideration of previously known and from newly identified calendrical polemics, this book offers new perspectives on internal tensions within Second Temple Judaism and their possible impact on the long standing debate about the day of the last supper.